Paediatric enteral tube feeding. Issue 8 (August 2017) - Burdall, Oliver C.; Howarth, Lucy J.; Sharrard, Alison; Lee, Alex C.H.
Abstract: The benefits of good nutritional status on outcomes of children with chronic illness have been well established. However, many neurologically impaired or chronically ill children and young people struggle to meet their energy requirements orally. In such cases an enteral feeding device inserted directly into the stomach and/or jejunum may be necessary for temporary or long term nutritional support. The decision to recommend a child for long term tube feeding is complex and needs to be balanced against the potential risks, and should involve multi-disciplinary input. We aim to review the current evidence for gastrostomy placement in order to clarify indications for referral for tube insertion, device selection, complications and their management.